Theophylline and anti-leukotrienes for the treatment of airway allergic diseases: theophylline - Boylan, Paul (Henry Stewart Talks, 2025)
Mechanism of action of theophylline, GOLD and GINA 2024 reports, Theophylline pharmacology, Low-dose theophylline, Bronchodilators